2007
DOI: 10.1152/jn.00270.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Inhibition of M-Current and Ethanol-Induced Direct Excitation of Ventral Tegmental Area Dopamine Neurons

Abstract: Ethanol-induced excitation of ventral tegmental area dopamine (DA VTA) neurons is thought to be critical for the reinforcing effects of ethanol. Although ligand-gated ion channels are known to be the targets of ethanol, ethanol modulation of voltage-dependent ion channels of central neurons has not been well studied. We have demonstrated that ethanol excites DA VTA neurons by the reduction of sustained K(+) currents and recently reported that M-current (I(M)) regulates action potential generation through fast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 45 publications
5
71
0
Order By: Relevance
“…3Bb). The non-I h effects of ethanol may be mediated by barium-sensitive potassium currents (McDaid et al 2008) and/or the M current (Koyama et al 2007). Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3Bb). The non-I h effects of ethanol may be mediated by barium-sensitive potassium currents (McDaid et al 2008) and/or the M current (Koyama et al 2007). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto et al (2006) demonstrated a clear link between ethanol-induced increases in the firing of mouse pacemaker DA neurons in vitro and the hyperpolarization-activated and cyclic nucleotidegated (HCN) channel current I h . In addition to its effects on I h , ethanol may also modify firing in DA VTA neurons through reduction of a barium-sensitive potassium current (Appel et al 2003;McDaid et al 2008) and M current (Koyama et al 2007).…”
mentioning
confidence: 99%
“…EtOH also decreases M-current (Koyama et al, 2007), and the effect of ACD on M-current is unknown. M-current is a voltage dependent, sustained potassium current that affects the firing frequency of dopaminergic VTA neurons (Koyama and Appel, 2006b).…”
Section: Differences Between Acetaldehyde and Alcohol: Electrophysiolmentioning
confidence: 99%
“…A study of the effects of EtOH on the ion channel responsible for M-current is one example of the difficulty in cataloging the effects of agents on ionic currents and then postulating a functional role for those currents on cell activity. EtOH reduces M-current of dopaminergic VTA neurons in a concentration-dependent manner (Koyama et al, 2007), but the selective M-current blocker XE-991 did not significantly reduce EtOH-induced excitation (Koyama et al, 2007). The effects of EtOH on M-current may be physiologically important in some processes, (for example, adaptation to chronic EtOH exposure), modulation of M-current does not alter the acute excitatory effect of EtOH.…”
Section: Differences Between Acetaldehyde and Alcohol: Electrophysiolmentioning
confidence: 99%
“…Neuronal M-current is a subthreshold voltage-gated K þ current encoded by Kv7/KCNQ channels that modulate firing frequency of mesencephalic dopamine neurons 14 and are functionally coupled to dopamine D2 receptors, providing essential modulatory inputs to their striatal and limbic targets 15,16 . Both Kv7/KCNQ channels and GHS-R are expressed in the SNc, hippocampus, dorsal root ganglion (DRG), hypothalamus and cortex 11,15,[17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%